Analisis Laporan Keuangan dan Penggunaan Altman Z-Score untuk Memprediksi Kebangkrutan Perusahaan Jasa Transportasi dan Logistik - Rusdi Hidayat, Ahmad; M. Nawawi, Zuhrinal; Syafina, Laylan (Universitas Muhammadiyah Metro, 2024)
This research aims to determine financial ratios that can be used as a tool to detect financial distress, which is a stage before bankruptcy and determine the level of bankruptcy in transportation and logistics service companies on the Indonesia Stock Exchange. This type of research is descriptive qualitative using documentation and literature study in data collection techniques. Financial reports, namely the balance sheet and profit and loss, are the object of this research. Four transportation and logistics service companies listed on the Indonesian Stock Exchange (BEI) and indexed on the Indonesian Sharia Stock Index are the subjects of this research. The research results show that financial ratios in financial statement analysis can detect financial distress and the modified Altman Z-Score method can predict bankruptcy. That there is one company in healthy condition, namely BIRD with an average Z-Score of 4.32. Meanwhile, three other companies, namely BLTA, TMAS and WEHA, are predicted to go bankrupt with respective Z-Scores of -54.26, 0.93 and -0.07.